WRITTEN GRAMMAR FEEDBACK ON STUDENTS’ WRITING WITH VISUAL LEARNING STYLE - Bradhiansyah Tri Suryanto (PEDAGOGIK : JURNAL PENDIDIKAN, 2018)
This research was intended to measure the effectiveness in the students’ writing achievement by using note-written and marked-written grammar feedback on students’ writing with visual learning styles. Based on the result of the computation, that in the experimental group using note-written grammar feedback, mean score for visual learning style is 78.78, while in the control group the visual learning style is 69.25. It means that there is a difference means score between experimental group and control group. Based on the statistical computation, the F value of Corrected Model was .519. It > .05 with the level of confidence 95% (α = .05). It means that was not valid. Further, the F value of Intercept was .000. It < .05 with the level of confidence 95% (α = .05). It means the dependent variable was not influenced by the independent variable. On the other words, the intercept was significant. While the effect of note-written grammar feedback to posttest score is .388. It > .05 with the level of confidence 95% (α = .05). It means that there is no a significance of note-written grammar feedback in students’ writing. Furthermore, for the technique on learning style was .347> .05 with the level of confidence 95% (α = .05). It means that there was no a significance of written grammar feedback techniques and students’ learning style on the students’ writing.